Self-bonding material prepared from secondary aluminum dross and preparation method and application thereof
Patent Information
- Application Number
- CN202410933821.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-12
AI Technical Summary
然而,目前的二次铝灰回收和再利用方法存在成本高、规模小、价值低、不能激发化学活性等缺点
[0022]1、本发明采用工业中较难消耗的二次铝灰与天然低成本风积沙作为原料,绿色环保。合成自胶结材料成本控制得当,原材料成本仅为22.5元/吨,胶结效果好,满足空心砖或砌块强度要求。
Smart Images

Figure CN118754475B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization technology, specifically relating to a self-bonding material prepared using secondary aluminum ash, its preparation method, and its application. Background Technology
[0002] Deserts are widespread globally, with nearly 41% of the Earth's land area degrading, affecting approximately 38% of the world's population. Natural aeolian sand (wind-deposited sand) is a sandy granular material formed by long-term soil drying and wind action. It is characterized by a loose structure, poor inherent stability, uneven particle size, and lack of defined edges. Its composition includes over 75% SiO2 and 5%–10% Al2O3. Sand is an indispensable raw material in the construction industry. It is estimated that 15 billion tons of sand are used in construction globally each year, most of which is manufactured sand and river sand due to their good uniformity and stability. Using aeolian sand in construction could reduce building material costs, improve the ecological environment, and align with the construction industry's trend towards ultra-low energy consumption and near-zero energy consumption. However, aeolian sand is difficult to use directly in construction projects due to severe weathering. Therefore, its application in social and industrial production is relatively limited; it must be activated before it can be used as a building material.
[0003] Currently, the main methods for utilizing aeolian sand involve solidification, where cement additives are typically used to improve strength and address issues of brittleness and low flexural strength. In concrete synthesis, 20%-30% aeolian sand is added to replace natural river sand as fine aggregate. The workability and strength of concrete can be improved by adjusting the ratio of aeolian sand to cement. Furthermore, the addition of bentonite, polymer emulsions, polypropylene fibers, and other additives improves the performance of building materials. Aeolian sand can also be chemically activated using microorganisms. Low doses of vinyl acrylate significantly improve the compaction and flexural cracking rate (BCR) of aeolian sand, while the addition of sodium thiosulfate improves unconfined compressive strength and flexural strength. The combination of enzyme-induced carbonate precipitation and polyvinyl alcohol-cured aeolian sand improves unconfined compressive strength, wind erosion resistance, water erosion resistance, and surface strength. Despite these advantages, high cost, limited availability in some areas, and lack of environmental friendliness still limit the widespread use of aeolian sand in engineering projects.
[0004] Primary aluminum ash is the insoluble slag produced during the electrolytic alumina process in the production of primary aluminum. Secondary aluminum ash is the aluminum-containing waste residue produced during the refining process of primary aluminum ash, and is the waste after the extraction of metallic aluminum from primary aluminum ash. Globally, more than 5 million tons of secondary aluminum ash are produced annually, of which approximately 95% is discarded in industrial solid waste dumps. Electrolytic aluminum processes are mature worldwide, and the chemical composition of secondary aluminum ash is similar across different regions. AlN is the main component of secondary aluminum ash, accounting for 10%-30%, and it also contains Al, Al2O3, Al4C3, MgO, and other forms, with elemental aluminum and its compounds accounting for over 70%. Typically, secondary aluminum ash is used in zeolites, ion exchangers, refractory materials, composite materials, cement, and concrete products. Current utilization methods mainly include pyrometallurgical and hydrometallurgical processes. In the hydrometallurgical process, AlN is hydrolyzed, and the salt dissolves in water, producing highly crystalline active alumina powder, high-purity nanostructured alumina powder, and layered double hydroxides. Pyrometallurgical methods involve calcining secondary aluminum ash with CaO to enhance its activity and reduce heavy metals, thereby producing glass ceramics. Furthermore, the recovery of Al2O3 and other value-added products can be achieved through a combination of acid leaching and calcination. However, current methods for recycling and reusing secondary aluminum ash suffer from drawbacks such as high cost, small scale, low value, and inability to activate chemical activity. Since 2021, China has classified secondary aluminum ash as hazardous waste, prohibiting direct landfill, making the resource utilization of secondary aluminum ash even more crucial. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a method for preparing self-cementing materials using secondary aluminum ash. This method uses secondary aluminum ash and aeolian sand as the main raw materials, and utilizes mechanical ball milling and chemical activation to enhance the potential activity of the mixture of aeolian sand and secondary aluminum ash. Finally, a green and environmentally friendly self-cementing material is synthesized under room temperature and high pressure conditions, realizing the comprehensive utilization of solid waste and providing a new solution for the disposal and resource utilization of aeolian sand and secondary aluminum ash.
[0006] To solve the above-mentioned technical problems, the method for preparing self-cementing materials using secondary aluminum ash provided by the present invention includes the following steps:
[0007] (1) Dry the aeolian sand, secondary aluminum ash and alkali activator to constant weight, wherein the alkali activator passes through a 200-mesh standard sieve.
[0008] (2) Add secondary aluminum ash, aeolian sand, and external alkali activator to the grinding jar of the planetary ball mill in sequence; the total mass of the secondary aluminum ash and aeolian sand is 100 parts by mass, of which the mass of the secondary aluminum ash is 45 to 55 parts by mass and the mass of the alkali activator is 3 to 6 parts by mass.
[0009] (3) Set the rotation speed and time of the planetary ball mill to 500-650 rpm and 20-30 min respectively, and carry out ball milling under these conditions.
[0010] (4) Pass the ball-milled mixed powder through a 2mm sieve to obtain a self-cementing material precursor.
[0011] (5) Add the self-bonding material precursor to the planetary cement mortar mixer. While the planetary cement mortar mixer is stirring at a low speed, slowly add water. The water addition time should be no less than 20 seconds and no more than 1 minute. Stop adding water when the moisture content of the mixture increases to 9-12%. Collect the generated ammonia gas during the water addition process. After the water addition is completed, adjust the planetary cement mortar mixer to a high speed and stir for 2-3 minutes.
[0012] (6) The above-mentioned uniformly mixed mixture is pressurized and molded at a loading rate of 5 to 7 kN / min. After the pressure is increased to 40 to 60 kN, the pressure is stopped and kept constant for 2 to 3 minutes. Then the pressure is released to obtain the self-bonding material.
[0013] (7) The self-adhesive material solidified block formed by high pressure is cured for no less than 14 days at a temperature of 20±1℃ and a humidity of 98±1%.
[0014] Preferably, the alkaline activator is at least one selected from CaO, quicklime, NaOH, and KOH.
[0015] Preferably, the mass of the alkali activator is 4 to 5 parts by mass.
[0016] Preferably, the secondary aluminum ash is 47-50 parts by weight.
[0017] Preferably, the ball milling speed is 500-550 rpm.
[0018] Preferably, the generated ammonia gas is collected and passed into concentrated sulfuric acid to form ammonium sulfate.
[0019] Preferably, the concentrated sulfuric acid is sulfuric acid with a concentration of 80% or higher.
[0020] The present invention also provides a self-adhesive material prepared by the above method and its application as a source of strength for hollow bricks or blocks.
[0021] Compared with traditional self-cementing materials, the secondary aluminum ash-aeolian sand co-preparation self-cementing material of the present invention has the following significant advantages:
[0022] 1. This invention uses secondary aluminum ash, which is difficult to consume in industry, and natural low-cost aeolian sand as raw materials, making it green and environmentally friendly. The cost of the synthesized self-cementing material is well controlled, with raw material costs of only 22.5 yuan / ton. It has good bonding effect and meets the strength requirements of hollow bricks or blocks.
[0023] 2. Compared with traditional self-bonding materials, the preparation process of this invention does not require calcination, and the molding process is quick and simple, greatly reducing the use of energy and natural resources. The molding process can be carried out in a factory, and the generated waste gas is collected and then passed into concentrated sulfuric acid to form ammonium sulfate, a valuable chemical product that can be used as a raw material for chemical fertilizers to generate secondary economic value.
[0024] 3. This invention utilizes secondary aluminum ash and aeolian sand, which are mechanically blended and ball-milled with an alkaline activator. During the ball milling process, physical activation and chemical modification occur, achieving the first chemical activation process. Physical activation alters the particle morphology and fineness, resulting in a more uniform particle composition. This facilitates filling pores during the synthesis of self-cementing materials, further improving material density. The aeolian sand contains over 75% SiO2, and the aluminum ash contains over 70% elemental aluminum and its oxide forms, along with MgO. The chemical modification process, under alkaline conditions, alters the internal mineral crystal structure of the material. This causes the stable Si-O, Al-O, and Mg-O bonds in the raw materials to break under high-energy mechanical forces and the resulting high temperatures, forming active silicon and aluminum monomers. This promotes the bonding of some Si-O-Al bonds, which, under blending conditions, form an active precursor, providing a foundation for further chemical activation.
[0025] 4. The self-cementing material in this invention is an active precursor that has undergone initial chemical activation. It then undergoes secondary chemical activation through mixing with water under high pressure. Under alkaline conditions, the original mineral structure is disrupted and reorganized, forming free ions such as AlO2 within the system. - and SiO3 2- This further promotes the formation of the Si-O-Al structure and continuously provides OH groups to the system. - This promotes the further progress of the chemical reaction. When all the free ions form a stable compound network structure (the molar ratio of active Si to active Al is 3:1 to 1:1), the framework structure of the material is formed, and a high-strength self-bonding material can be obtained.
[0026] 5. This invention creatively uses secondary aluminum ash and aeolian sand as raw materials, revealing the intrinsic connection between "secondary activation-chemical activation-structural reorganization," and establishing a method for directional control of the strength of self-cementing materials. This ensures that all chemical components in the raw materials participate in the chemical reaction, achieving the purpose of chemically activated consolidation and forming a more stable solidified body with greater stability. This differs significantly from the traditional self-cementing materials that achieve stable strength through physical encapsulation.
[0027] 6. Desert regions often experience extreme weathering environments, which places higher demands on the stability of materials. The self-cementing material prepared by this invention using secondary alumina ash and aeolian sand as the main raw materials meets this requirement. The self-cementing material conforms to the Chinese national standard "Sintered Hollow Bricks and Blocks" (GB13545-2014). This method overcomes the limitations of traditional aeolian sand-based materials and improves strength and durability.
[0028] 7. This invention uses manufactured sand and secondary alumina ash to synthesize a self-cementing material for comparison. However, because the manufactured sand particles are uniformly distributed, while the self-cementing material generates many irregular pores during its formation process, these pores cannot be filled. This results in a compressive strength that is more than 30% lower than that of the self-cementing material synthesized from aeolian sand and secondary alumina ash. The self-cementing material synthesized from aeolian sand and secondary alumina ash has a significant strength advantage.
[0029] 8. The self-bonding material of this invention has been applied on a small scale. During a 360-day test, the compressive strength continued to rise to 8.57 MPa, demonstrating good long-term stability and durability. Furthermore, the heavy metal leaching concentration meets the Chinese standard "Environmental Quality Standard for Surface Water" (GB 3838-2002), thus satisfying environmental requirements. Attached Figure Description
[0030] Figure 1 This is a flowchart illustrating the preparation process of the self-adhesive material of this invention.
[0031] Figure 2 This diagram illustrates the effect of different ball milling speeds on particle size distribution of the raw materials used in this invention during the ball milling process.
[0032] Figure 3 The diagram shows the compressive strength of self-cemented materials at different ages under different ball milling speeds.
[0033] Figure 4 This is a graph showing the functional relationship between the compressive strength of self-cementing materials and the ball milling speed.
[0034] Figure 5 The graph shows the grinding kinetics fitting of the precursor RRB model and Swrebec model under different ball milling speeds.
[0035] Figure 6 This is an XRD mineral composition diagram of a self-cementing material.
[0036] Figure 7 This is the SEM-EDS (scanning electron microscopy-energy dispersive spectroscopy) spectrum of the self-cementing material.
[0037] Figure 8 This is the XPS photoelectron spectrum of the self-cementing material.
[0038] Figure 9This is a diagram illustrating the mechanism of chemical activation processes in self-cementing materials.
[0039] Figure 10 This is the infrared spectrum of the self-cementing material.
[0040] Figure 11 The graph shows the compressive strength and ammonia nitrogen leaching concentration of the self-cementing material in field tests.
[0041] Figure 12 A comparison chart of the properties of aeolian sand / manufactured sand self-cementing materials. Detailed Implementation
[0042] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0043] Example 1
[0044] Figure 1 This is a process flow diagram for preparing the self-cementing material of the present invention, wherein the alkali activator is exemplified by calcium oxide in the figure. The chemical composition of aeolian sand and secondary alumina ash in this embodiment is shown in Table 1. In this embodiment, the aeolian sand accounts for 50% of the mass of the added secondary alumina ash and aeolian sand raw materials, and the external dosage of the alkali activator CaO is 5% (i.e., 5% of the total mass of secondary alumina ash and aeolian sand). Under the condition of ball milling time set to 25 min, the precursor was obtained after ball milling at 450 / 500 / 550 / 600 / 650 rpm. The particle size distribution was determined using a laser particle size analyzer (Dandong Better Instruments Co., Ltd., 9300ST, China), with experimental factors as shown in Table 2. Figure 2 As shown, with the ball milling speed increasing from 450 rpm to 500 rpm, the medium particle size (D50) of the material showed a slight increase of 12.84%. At a ball milling speed of 550 rpm, the D50 value of the precursor remained relatively stable. However, with further increases in ball milling speed, especially at 650 rpm, the D50 of the precursor increased significantly to 34.33 μm. The variation of the average particle size (MGD) was similar to that of D50. Influenced by particle hardness, material composition, and other factors, rapid ball milling speed increased the collision frequency of aeolian sand and secondary aluminum ash with the steel balls in the ball mill, leading to particle agglomeration and an increase in D50 and MGD.
[0045] Table 1. Chemical composition (%) of aeolian sand and secondary alumina ash determined by X-ray fluorescence spectrometry.
[0046]
[0047] Note: NAS refers to aeolian sand, and SAD refers to secondary aluminum ash.
[0048] Table 2 Test conditions
[0049]
[0050] After ball milling, water was slowly added to the mixture at a low speed (140±2 rpm, 62±2 rpm) using a planetary cement mortar mixer to adjust the moisture content to 11% (water addition time: 40±10 seconds). Then, the planetary cement mortar mixer was rapidly stirred at a high speed (285±3 rpm, 125±3 rpm) for 2 minutes. Ammonia gas released upon contact with water was collected using a suction device and passed into sulfuric acid to generate ammonium sulfate for fixation. 200g of the mixture was weighed and placed... In a cylindrical stainless steel mold, the material is pressed and formed under an external pressure of 40 kN for 15 seconds, and then demolded to obtain a self-adhesive material. It is then cured for 3–14 days under standard conditions (temperature: 20 ± 1℃, humidity: 98 ± 1%).
[0051] like Figure 3 As shown, after 14 days of curing, the compressive strength of R1 was 3.19 MPa. The compressive strength showed a significant increase with increasing ball milling speed.
[0052] like Figure 4 As shown, by fitting the compressive strength and ball milling speed with a quadratic polynomial, the R of the self-adhesive material after 14 days of curing was determined. 2 The value was 0.97. When the ball milling speed reached 550–650 rpm, the compressive strength remained stable between 6.19 and 6.90 MPa. Although the compressive strength reached its highest value at 600 rpm, higher speeds increased the activation cost. Considering both economic factors and experimental results, 550 rpm was determined to be the most suitable choice for mechanical activation.
[0053] Figure 5 The figures show the grinding kinetics fitting diagrams of the precursor using the RRB and Swrebec models under different ball milling speeds. The particle size distribution characteristics of the material play an important role in chemical excitation and compressive strength. By investigating the particle size distribution characteristics of the material at different ball milling speeds, the relationship between particle size distribution and compressive strength is further analyzed.
[0054] The RRB model correctly predicted the particle distribution pattern of the precursor. 2 The value is greater than 0.99. The precursor particle size distribution fitted by the RRB model is in close agreement with the measured value, confirming the applicability of the RRB model to the precursor particle size distribution. Furthermore, with increasing grinding speed, the characteristic particle size (d*) increases from 41.35 μm to 57.43 μm. The increased grinding speed causes larger particles to break down into smaller particles, leading to particle agglomeration and the formation of "secondary particles," exhibiting loose aggregates. These "secondary particles" show good gradation distribution during chemical activation, promoting hydration reactions and contributing to improved compressive strength.
[0055] R obtained by fitting the Swrebec model 2 The values range from 0.984 to 0.988, slightly lower than those of the RRB model. Although the D50 predicted by the Swrebec model is consistent with the measured value, the predicted maximum particle size fluctuates significantly, showing a deviation from the measured value. Furthermore, the b-value initially increases and then decreases, indicating substantial fluctuations in the particle size distribution curve. Therefore, the Swrebec function further demonstrates that ball milling speed can influence the chemical activity of the material and the rationalization of its particle size distribution.
[0056] The self-cementing material was characterized by XRD mineral composition analysis, such as... Figure 6 As shown, in secondary alumina, the main crystalline phases are Al and AlN, with diffraction peaks of Fe and spinel also present. In aeolian sand, quartz diffraction peaks are accompanied by the presence of albite and alumina. However, in self-cementing materials, the diffraction peaks of quartz and albite are weakened, and no new crystal structures are formed. This phenomenon can be attributed to the large amount of relatively stable crystalline material in aeolian sand. Under the combined effect of mechanical collision and high temperature during ball milling, the mineral lattice of secondary alumina produces more defects and damage than that of aeolian sand. The addition of CaO and water creates an alkaline environment, promoting the excitation and recombination of chemical bonds and producing amorphous materials. In addition, the observation of broad peaks between 18 and 25 degrees and weakened diffraction peaks of mineral phases in self-cementing materials indicates the presence of amorphous materials, which is also the reason why self-cementing materials have a certain strength.
[0057] Scanning electron microscopy (SEM) tests were performed on secondary aluminum ash, aeolian sand, and self-cementing materials, such as... Figure 7 As shown. Secondary aluminum ash ( Figure 7 a and local magnification Figure 7 b) exhibits a relatively rough surface, characterized by rod-shaped and flaky fragments with loose filling material and numerous pores. The surface elemental distribution indicates the presence of a significant amount of aluminum. Figure 7 i). The results explain why secondary alumina ash can be easily broken into smaller particles by mechanical force and its excellent cementing properties. Aeolian sand ( Figure 7 c and local magnification Figure 7 d) It is mainly composed of large, irregularly shaped particles with a highly dense microstructure. This is determined by its chemical composition (Table 1) and mineral structure (…). Figure 6 )Analysis determined Figure 7 The agglomerates observed in d are primarily quartz (silicon dioxide), a mineral with high hardness and mechanical strength. However, these agglomerates can provide Si (Si) during chemical activation. Figure 7 j), which has great potential for the preparation of self-adhesive materials.
[0058] Self-adhesive materials Figure 7The microstructure of e, 7g) shows tightly packed particles with unreacted debris adhering to the surface. In the magnified view ( Figure 7 f, 7h), the surface exhibits a disordered amorphous structure, representing the gel-like microstructure of hydration products. This structure contributes to the high compressive strength of the self-cementing material. EDS energy dispersive spectroscopy analysis further confirms the presence of a large amount of silicon, aluminum, and oxygen elements together (f, 7h). Figure 7 Furthermore, the surface of the fragments exhibits a dense, sheet-like structure (k). Figure 7 f) It has a metallic luster in its morphology. This appearance is significantly different from that of secondary aluminum ash and aeolian sand at the same magnification, confirming that mechanochemical activation has led to a fundamental change in the mineral structure.
[0059] XPS photoelectron spectroscopy analysis was performed on aeolian sand, secondary aluminum ash, and self-cementing materials. Figure 8 In the XPS photoelectron spectra of silicon and aluminum, we found that silicon in aeolian sand exists in the form of silicon dioxide (102.80 eV). Figure 8 a). Aluminum in secondary aluminum ash exists in the forms of Al2O3 / Al (74.80 eV) and AlN (73.50 eV). Figure 8 (b) The results are consistent with the XRD mineral composition analysis. No characteristic absorption peaks for SiO2 and AlN were detected in the self-cementing material, but Al2SiO5 (102.70 eV) and SiO2 (Al2O3) peaks were observed. 0.55 (102.20 eV), Al2O3 (73.24 eV) and SiO2 (Al2O3) 0.22 The new characteristic absorption peak (74.30eV) Figure 8 (c and 8d). This finding indicates that most Si-O chemical bonds and Al-N bonds are broken by alkali erosion, forming active silicon and aluminum monomers, ultimately resulting in a more stable structure (Si-O-Al).
[0060] Alkali activators promote chemical activation. The original secondary aluminum ash and aeolian sand have low content and low calcium content, resulting in indistinct characteristic absorption peaks. In the self-cementing material prepared using calcium oxide as an alkali activator in this embodiment, Ca 2p 3 / 2 exists as Ca-SiO3 (347.04 eV) and Ca2[Mg5][Si8O 22 It exists in the form of OH2 (347.70 eV). Figure 8 e).
[0061] The Ca-O bonds in calcium oxide break under mechanochemical action. In an alkaline solution environment, the Si-O bonds in aeolian sand and the Al-N bonds in secondary alumina ash undergo hydrolytic breakage to form SiO3. 2- AlO3 3-And free substances such as Si and Al active monomers, and Ca4 2- They jointly undergo coordination and recombination reactions, forming stable compound structures such as Al₂SiO₅ and CaSiO₃. The hydration reaction of CaO also provides an alkaline environment for the system and promotes chemical activation. Figure 9 )
[0062] The Al₂O₃ binding energy of the self-cementing material is 73.24 eV, which is lower than that of secondary aluminum ash. This indicates that aluminum-containing substances are also undergoing transformation, and some Al-O bonds are involved in the chemical reaction. This conclusion was verified by infrared spectroscopy. Figure 10 In aeolian sand, 879cm -1 The absorption wavelength is the vibrational peak of the silicon-oxygen bond in SiO2 (δSi-O-Si / νSi-O). However, in self-cementing materials, this characteristic absorption peak shifts to 779 cm⁻¹. -1 This indicates a change in the silicon-oxygen bond, which, combined with mineral composition analysis, confirms is a result of a hydration reaction. Furthermore, in the self-cemented material diagram at 511 cm⁻¹... -1 A new absorption peak (Si-O-Al) appeared at the absorption wavelength. Given the abundance of Al and AlN atoms in the secondary aluminum ash, Al participates in the chemical reaction and combines with Si and O to form stable chemical bonds. Since the chemical reaction is a hydration process under alkaline conditions, the absorption wavelength of the hydroxyl peak of water decreased (1631 cm⁻¹). -1 The absorption wavelength of the hydroxyl peak of the hydrated product bound to water increases (3452 cm⁻¹). -1 This indicates that alkali activation promotes hydroxylation. Therefore, during the preparation of environmentally friendly self-cementing materials using these materials, a chemical cementation reaction occurs in the internal mineral structure during the ball milling and maintenance stages.
[0063] Example 2
[0064] This embodiment involved field testing in a desert region. The self-cementing material synthesized indoors (prepared in Example 1, with ball milling at 550 rpm and curing for 14 days) was placed in a desert area as a road shoulder material for desert roads, achieving good results. Figure 11 a) During the 360-day test, the compressive strength consistently increased to 8.57 MPa. The leaching of ammonia nitrogen from the self-bonded material showed a significant decreasing trend. Figure 11 b).
[0065] Examples 3-9
[0066] The only difference between Examples 3, 4 and 5 and Example 1 is that the content of aeolian sand is changed to 40%, 45% and 55% by mass, respectively, and the ball mill speed is 550 rpm. All other conditions are the same as in Example 1.
[0067] The only difference between Examples 6 and 7 and Example 1 is that the alkaline activator is replaced with solid NaOH and KOH, respectively, and the ball milling speed is 550 rpm. All other conditions are the same as in Example 1.
[0068] The only difference between Examples 8 and 9 and Example 1 is that water was added to the planetary cement mortar mixer to adjust the moisture content to 9% and 12% respectively, and the ball mill speed was 550 rpm. All other conditions were the same as in Example 1.
[0069] The self-adhesive materials prepared in Examples 3-9, after 14 days of curing, had compressive strengths of 4.23 MPa, 5.10 MPa, 6.11 MPa, 5.46 MPa, 5.60 MPa, 5.04 MPa, and 5.82 MPa, respectively.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is that manufactured sand is used instead of aeolian sand to prepare the self-cementing material. The mass ratios of secondary aluminum ash and manufactured sand in the self-cementing material of this comparative example are 50% and 50% respectively, and CaO is added at a mass ratio of 5% of the total mass. All other process steps are the same as in Example 1.
[0072] The compressive strengths of aeolian sand-secondary alumina ash and manufactured sand-secondary alumina ash self-cementing materials are respectively as follows: Figure 12 a, Figure 12 As shown in b, the compressive strength of the self-cementing material is significantly higher than that of the self-cementing material made from manufactured sand and secondary alumina ash (under the same ratio of secondary alumina ash). After 14 days of curing, the compressive strength of the self-cementing material made from manufactured sand and secondary alumina ash is 5.13 MPa. This comparative example also shows the strength changes of self-cementing materials prepared under different ratios of aeolian sand and secondary alumina ash. Among them, the self-cementing material prepared with a mass ratio of aeolian sand and secondary alumina ash of 1:1 has the highest strength. However, the strength development of the self-cementing materials prepared under various ratios mainly occurs within 0-3 days. Figure 12 a), while the strength growth of the self-cementing material made from machine-made sand and secondary aluminum ash mainly occurs within 7-14 days. Figure 12 b). The compressive strength after 14 days of curing is 3.1 times higher than that after 3 days of curing.
[0073] SEM images of self-cementing materials of aeolian sand-secondary alumina and manufactured sand-secondary alumina ( Figure 12 c and Figure 12Significant differences were observed in d). The surface of the self-cementing material was highly dense, while the surface of the manufactured sand-secondary aluminum ash self-cementing material consisted of an amorphous gel-like material with an uneven particle distribution. The particles were connected by an irregular fibrous gel structure with dense pores and obvious cavities. Due to the artificial mechanical synthesis of manufactured sand, the macroscopic structural differences between particles were small, and the particle size distribution was relatively uniform. Therefore, the irregular gaps in the manufactured sand-secondary aluminum ash self-cementing material could not be effectively filled. Under external forces, the structure was prone to fracture and deformation, which is one of the reasons for the lower strength of the manufactured sand-secondary aluminum ash self-cementing material.
[0074] Comparative Example 2
[0075] The difference between this comparative example and Example 1 is that the water addition time is shortened to 2 seconds and 2 minutes, and the ball mill speed is 550 rpm; all other process steps are the same as in Example 1. After 14 days of curing, the compressive strengths of the aeolian sand-secondary aluminum ash self-cementing materials were tested and found to be 4.31 MPa and 4.80 MPa, respectively.
[0076] As can be seen from the self-bonding material molding process, when the water addition time is shortened to 2 seconds, heat is rapidly released during stirring, and the surface temperature of the stirring pot rises significantly to over 50°C. Due to the temperature rise, some water vaporizes and escapes, so the actual water content participating in the reaction is lower than the design value, resulting in lower compressive strength. When the water addition time is extended to 2 minutes, the stirred material gradually agglomerates into small granules with a diameter of 0.5–1.5 cm. The structure is relatively loose, and the chemical reaction is incomplete, resulting in lower compressive strength.
Claims
1. A method for preparing self-cementing materials using secondary aluminum ash, characterized in that: The method includes the following steps: 1) Dry the aeolian sand, secondary aluminum ash and alkali activator separately to constant weight, wherein the alkali activator passes through a 200-mesh standard sieve; 2) Add secondary aluminum ash, aeolian sand, and external alkali activator sequentially to the grinding jar of the planetary ball mill; the total mass of the secondary aluminum ash and aeolian sand is 100 parts by mass, of which the mass of secondary aluminum ash is 45-55 parts by mass and the mass of alkali activator is 3-6 parts by mass. 3) Set the rotation speed and time of the planetary ball mill to 500~650 rpm and 20~30 min respectively, and carry out ball milling under these conditions; 4) Pass the ball-milled mixed powder through a 2 mm sieve to obtain a self-cementing material precursor; 5) Add the self-cementing material precursor to the planetary cement mortar mixer. While the planetary cement mortar mixer is stirring at a low speed, slowly add water. The water addition time should be no less than 20 seconds and no more than 1 minute. Stop adding water when the moisture content of the mixture increases to 9-12%. Collect the generated ammonia gas during the water addition process. After the water addition is completed, adjust the planetary cement mortar mixer to a high speed and stir for 2-3 minutes. 6) Press the uniformly mixed mixture at a loading rate of 5~7 kN / min to form a self-bonding material. After the pressure is increased to 40~60 kN, stop pressing and maintain a constant pressure for 2~3 min. Then release the pressure to obtain the self-bonding material.
2. The method for preparing self-cementing materials using secondary aluminum ash according to claim 1, characterized in that: The alkaline activator is at least one of CaO, NaOH, and KOH.
3. The method for preparing self-cementing materials using secondary aluminum ash according to claim 1 or 2, characterized in that: The mass of the alkaline activator is 4-5 parts by mass.
4. The method for preparing self-cementing materials using secondary aluminum ash according to claim 1 or 2, characterized in that: The secondary aluminum ash has a mass of 47-50 parts by weight.
5. The method for preparing self-cementing materials using secondary aluminum ash according to claim 1 or 2, characterized in that: The ball mill rotation speed is 500~550 rpm.
6. The method for preparing self-cementing materials using secondary aluminum ash according to claim 1 or 2, characterized in that: The collected ammonia gas is passed into concentrated sulfuric acid to form ammonium sulfate.
7. The method for preparing self-cementing materials using secondary aluminum ash according to claim 6, characterized in that: The concentrated sulfuric acid mentioned is sulfuric acid with a concentration of 80% or higher.
8. The self-adhesive material prepared by the method according to any one of claims 1 to 7.
9. The application of the self-adhesive material of claim 8 as building blocks.
10. The application according to claim 9, characterized in that: Self-adhesive materials need to be cured before use. The curing temperature is 20±1℃, the humidity is 98±1%, and the time is no less than 14 days.
Citation Information
Patent Citations
Process for preparing baking-free brick by taking secondary aluminum ash as raw material under high pressure
CN114409364A
Secondary aluminum ash for concrete and treatment method thereof
CN115180857A